Optimal design and experimental evaluation of a TLP for FOWT at moderate water depth - Meng, X.; Liu, X.; Tian, H.; Liu, M.; Wu, Changzhi (2016)
An improved reduction model is constructed to interpret coupled dynamic properties of an integrated support system for floating offshore wind turbine (FOWT), which is built up by a turbine, a tower, a typical tension leg platform (TLP) floater and tendons. A customized optimization program is developed for typical TLP-type 5MW FOWTs in moderately deep water. Parameterized designs are evaluated including slow-drift, sum-frequency effects from environmental loads and dynamic resonance excitation from turbines. The performance and constrains of the system, especially the pre-stress state of tendons are implemented as additional optimal restrictions to make sure feasible results sound at extreme conditions. A physical model experiment with main structural parameters is conducted according to the sensitivity analysis to evaluate optimal concepts. The paper presents an effective methodology to determine dimensions of components for TLP type of FOWT with specific optimization approach.